Einstein's mistakes : the human failings of genius - Ohanian, Hans C. (New York: W.W. Norton & Company, 2008)
Ohanian offers insights into aspects of Albert Einstein that many don't usually consider: his mistakes and the role they played in the discovery of his theories.
Chronology of Einstein's mistakes -- I will resign the game -- A lovely time in Berne -- And yet it moves -- If I have seen farther -- A storm broke loose in my mind -- Motions of inanimate, small, suspended bodies -- What is the light quantum? -- The argument is jolly and beguiling -- Suddenly I had an idea -- The theory is of incomparable beauty -- The world is a madhouse -- Does God play dice? -- The graveyard of disappointed hopes -- Postmortem.
Includes bibliographical references (p. 339-373) and index.
Keywords: Einstein, Albert, -- 1879-1955.; Physics -- History; Physics -- Philosophy; Science -- History